2009
DOI: 10.1007/s00392-009-0056-7
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine-induced maximal coronary hyperemia for myocardial fractional flow reserve measurements: comparison of administration by femoral venous versus antecubital venous access

Abstract: The intravenous application of adenosine via antecubital venous access is feasible but slightly less effective than the femoral approach. In this setting, an antecubital dosage of 170 microg kg(-1) min(-1) is comparable to the standard dosage of 140 microg kg(-1) min(-1) in the femoral vein. In some patients, this regimen might prevent an underestimation of lesion severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The former approach has been shown in a single study to produce significantly lower FFR recordings when comparing an adenosine infusion rate of 140 mg/kg/min with a rate of 170 mg/kg/min via the antecubital fossa (13). The former approach has been shown in a single study to produce significantly lower FFR recordings when comparing an adenosine infusion rate of 140 mg/kg/min with a rate of 170 mg/kg/min via the antecubital fossa (13).…”
Section: Ffr In the Transradial Eramentioning
confidence: 99%
“…The former approach has been shown in a single study to produce significantly lower FFR recordings when comparing an adenosine infusion rate of 140 mg/kg/min with a rate of 170 mg/kg/min via the antecubital fossa (13). The former approach has been shown in a single study to produce significantly lower FFR recordings when comparing an adenosine infusion rate of 140 mg/kg/min with a rate of 170 mg/kg/min via the antecubital fossa (13).…”
Section: Ffr In the Transradial Eramentioning
confidence: 99%
“…Second, we routinely induced hyperemia using adenosine through the forearm (antecubital) vein, and not through the central (femoral) vein. In the study by Lindstaedt et al,13) this method was slightly less effective than that of femoral vein infusion. However, recent studies by De Bruyne et al14) and Seo et al15) have shown that hyperemic efficacy of adenosine does not differ between infusion into the central vein and peripheral vein.…”
Section: Discussionmentioning
confidence: 92%
“…Another alternative access for adenosine infusion can be a large peripheral vein. Lindstaedt et al 21 compared the hyperemic efficacy of adenosine infusion between the femoral vein and the antecubital vein. They found that a 140 g/kg/min infusion of adenosine via the antecubital vein was slightly less effective than the femoral vein infusion; however, the mean difference of FFR between the antecubital vein and femoral vein infusions was just 0.0126.…”
Section: Discussionmentioning
confidence: 99%